Regenerative Approach to Bilateral Rostral Mandibular Reconstruction in a Case Series of Dogs - Arzi, Boaz; Cissell, Derek D.; Pollard, Rachel E.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2015)
Extensive rostral mandibulectomy in dogs typically results in instability of the mandibles that may lead to malocclusion, difficulty in eating and drinking, food prehension, and pain of the temporomandibular joint. Large rostral mandibular defects are challenging to reconstruct due to the complex geometry of this region. In order to restore mandibular continuity and stability following extensive rostral mandibulectomy, we developed a surgical technique using a combination of intraoral and extraoral approaches, a locking titanium plate and a compression resistant matrix (CRM) infused with rhBMP-2. Furthermore, surgical planning that consisted of computed tomographic (CT) scanning and 3D model printing were utilized. We describe a regenerative surgical technique for immediate or delayed reconstruction of critical-size rostral mandibular defects in 5 dogs. Three dogs had healed with intact gingival covering over the mandibular defect and had immediate return to normal function and occlusion. Two dogs had the complication of focal plate exposure and dehiscence, which was corrected with mucosal flaps and suturing; these dogs have since healed with intact gingival covering over the mandibular defect. Mineralized tissue formation was palpated clinically within 2 weeks and solid bone formation within 3 months. Computed tomography findings at 6 months postoperatively demonstrated that the newly regenerated mandibular bone had increased in mineral volume with evidence of integration between the native bone, new bone and CRM compared to the immediate postoperative CT. We conclude that rostral mandibular reconstruction using a regenerative approach provides an excellent solution for restoring mandibular continuity and preventing mandibular instability in dogs.